Natural polymers for consolidation of the Oseberg artefacts - Wakefield, Jennifer (2021)
Conservation is of vital importance for museums. The Viking Ship Museum has a particular problem in terms of conservation. It houses artefacts from the Oseberg Viking ship burial that are of great significance in terms of Viking history and are of national pride to Norway. These artefacts were buried in 834 AD, excavated in 1904, treated with alum and dried. The alum treatment, which started in 1905, led to them becoming acidic (pH 1-2), resulting in severe degradation of the artefacts. Current conservation methods have their limitations due to the alum previously used to conserve these artefacts, the removal of which could cause some of the most fragile artefacts to collapse entirely. However, some of the less fragile artefacts could cope with a water treatment. Even in that case, PEG, the most commonly used aqueous conservation treatment, may not be suitable due to the high concentration of acid and metal ions in some artefacts. Natural polymers pose some advantages to traditional methods in terms of sustainability and future use, so, for this reason, chitosan was initially investigated. Additionally, chitosan contains amine groups which may help to increase the pH and aid in metal chelation and in preventing hydrolysis reactions. The molecular weight of potential consolidants was determined with an analytical ultracentrifuge prior to wood treatment to determine the likelihood of wood penetration. This was followed by testing on artificially degraded wood and on archaeological wood. Chitosan gave good results in wood treatment tests, however, the use of acid for the dissolution of chitosan is a concern, hence, despite obtaining good results, an alternative aqueous treatment was sought. Chitosan acetate salt and aminocellulose were researched using the same methodology. Chitosan acetate salt did not aid in consolidation. Aminocellulose produced good results for conservation, appearing suitable either alone or in combination with PEG and has potential advantages to PEG, although the long-term stability needs to be assessed.